Factors influencing the intention to use electric cars in Brazil - Buranelli de Oliveira, Marina [UNESP]; Moretti Ribeiro da Silva, Hermes [UNESP]; Jugend, Daniel [UNESP]; De Camargo Fiorini, Paula; Paro, Carlos Eduardo (Elsevier, 2022)
Electric cars have been gaining ground on the world market in recent years. In Brazil, the presence of this new technology is still nascent and few studies on the subject are found in the literature, especially in terms of consumer perspectives. This research aimed to identify the determining factors for the Intention to Use electric cars in Brazil, adopting a research model based on the Decomposed Theory of Planned Behavior and the influence of consumer emotions. Data was collected from an online survey of 488 Brazilian respondents and analyzed using the Structural Equation Modeling technique. The results reveal that a perceived relative advantage and a perceived compatibility associated with the use of the electric car have a positive effect on the attitudes of the respondents, and that positive attitudes towards the electric car have, in turn, a positive effect on the Intention to Use the same. Attitudes towards the electric car and the influence of emotions were identified as the biggest predictors of Intention to Use. The results also indicate that, despite the positive inclination of respondents in relation to using and even buying an electric car, there is still much concern about the charging infrastructure, charging time and vehicle autonomy, in addition to other barriers, such as the purchase price. These findings are in line with the results of several studies of the same scope, carried out in other countries. The results of the present study may shed light on the discussion of the topic in Brazil, in addition to providing stakeholders in electromobility in the country with information that benefits the development of policies and guidelines for the spread of electric car use in Brazil.
Keywords: Adoption of New Technologies; Electric Cars; Electromobility in Brazil; Intention to Use; Structural Equation Modeling; Theory of Planned Behavior